On the Digital Path of the Protection of Folk Houses in Qiang Nationality Villages from the Perspective of Digital Media Technology - Dan Hu; Li Zhang; Xiaona Shi; Xiaoxi Ma; Zhudan Pang (Advances in Multimedia)
In order to better adapt to the development nationalities of the digital media era and promote the inheritance path innovation of traditional nationality cultural resources, this study takes Qiang nationality village houses as the research object and takes the digital media era as the research background to deeply analyze the inheritance and protection path of Qiang nationality village house culture in the digital era. Therefore, this paper proposes a method of digital protection path of minority residential buildings based on point cloud technology and BIM Technology. This method constructs the digital resource database of village residential buildings by constructing the BIM model and the three-dimensional model of point cloud technology and then constructs the building information model based on traditional residential buildings from the data of building model, graphic influence, and cultural attributes, so as to provide technical support for the protection, repair, and reconstruction of ethnic minority buildings and the inheritance of ethnic culture.